Active Control of Vehicle Suspension System Having Driver Model via L2 Gain State Derivative Feedback Controller - Sever, Mert; Yazici, Hakan (IEEE, 2017)
This paper is concerned with the design of an L-2 gain state derivative feedback controller for an active suspension system with driver model. A five-degree-of-freedom model having an integrated vehicle seat, a seated human body and a quarter vehicle is used to analyze ride comfort, safety requirements and power consumption. In order to investigate effectiveness of proposed method, performance of the L-2 gain state derivative feedback controller is compared with conventional state feedback controller. IS02631 random road disturbances are used to simulate random road irregularities. Numerical simulation studies show that proposed state derivative feedback controller offers similar level of performance improvement with more practicable feedback strategy when compared with state feedback counterpart.
Keywords: state derivative feedback; active vehicle suspensions; seated driver model; linear matrix inequalities; L-2 gain control; H-INFINITY CONTROL; MULTIOBJECTIVE CONTROL; DESIGN; Engineering